Exploring Perceptions and Experiences: Integrating AI in English Language Teaching from the Perspectives of Learners and Educators - Suharno, Suharno; Musthafa, Bachrudin; Purnawarman, Pupung (Jurnal Pendidikan Progresif, 2025)
Exploring Perceptions and Experiences: Integrating AI in English Language Teaching from the Perspectives of Learners and Educators. Purpose: This study aims to explore learners’ and faculty members’ perceptions of the enactment of Artificial Intelligence (AI) technologies in English Language Teaching (ELT) based on the Community of Inquiry (CoI) Framework; in particular, intending to investigate the perceived benefits, challenges, and pedagogical implications of artificial intelligence adoption in the Indonesian education landscape. Methods: Using a mixed-methods sequential explanatory design, the study commenced with quantitative data collection through questionnaires issued to learners and educators. The next phase involved qualitative data collection through in-depth interviews and focus group discussions, which provided greater depth of insight into participants’ experiences and attitudes. Findings: In this sense, it is significant that the positive impact of artificial intelligence on ELT was reported above. Educators also acknowledged the role of AI in enhancing traditional practices and facilitating classrooms that are more dynamic and student-centered. Nonetheless, there are concerns about privacy, data security, and whether AI-driven tools are culturally nuanced enough for language instruction. Conclusion: Such fears underscore the need for contextually appropriate implementation guidelines that adapt AI tools to align with pedagogy norms and moral codes found in local education systems. This work thus contributes to the growing literature on the implementation of AI technology in language education by providing empirical evidence of effective integration of this technology, particularly in Indonesia. The outcomes will serve not solely to inform educators and policymakers on the best practices surrounding AI integration throughout ELT but also to affirm the addressing of protection and cultural acclimatization challenges. Overall, the research sets forth a roadmap for AI’s potential pedagogical role in shaping language instruction practice and policy. Keywords: artificial intelligence, community of inquiry, english language teaching, experiences, perceptions.